Lalu Muhammad Guawan - Lalu Muhammad Gunawan; Lalu Sapta Wijaya Kusuma; Yulfiras Thariqi (Jurnal Porkes, 2026)
This research was conducted to examine the influence of footwork training on the agility and speed of badminton athletes at PB. AIKMUAL Praya Lombok Tengah. The study applied an experimental method employing a One Group Pretest–Posttest Design. The population involved 20 badminton athletes, while the research sample was determined through purposive sampling according to specific criteria established by the researcher. The training program was implemented over 18 sessions with a training frequency of three times per week. Agility was measured using the shuttle run test, whereas speed was assessed through the 30-meter sprint test. The collected data were analyzed using normality testing, homogeneity testing, and paired sample t-test analysis. The findings indicated that footwork training significantly improved the athletes’ agility and speed. After participating in structured and systematic footwork exercises, the athletes demonstrated better movement coordination, faster reaction time, and more efficient court movement. Based on these findings, it can be concluded that footwork training provides a positive contribution to enhancing the physical performance of badminton athletes, particularly in terms of agility and speed at PB. AIKMUAL Praya Lombok Tengah.